Sneddon- Wilkinson Disease in association with Non- Hodgkin Lymphoma - Jha, A; Kumar, A; Gurung, D; Chaurasia, AK; Das, AK; Pokharel, DB (Journal of Institute of Medicine Nepal, 2008)
Sneddon-Wilkinson disease is a rare condition with chronic recurrent course. It may be a part of paraneoplastic manifestation of underlying malignancy. The disease is diagnosed on the basis of its characteristic clinical features and histopathology. A case of Sneddon -Wilkinson disease associated with non-hodgkin lymphoma in a 54 years old lady is presented. Key words: Sneddon-Wilkinson disease, Non-Hodgkin lymphoma, Paraneoplastic manifestation, Dapsone. Journal of Institute of Medicine, April, 2008; 30:1 59-61 The full text of this paper is available from the Journal of Institute of Medicine website